2015
DOI: 10.14419/ijet.v4i4.5139
|View full text |Cite
|
Sign up to set email alerts
|

Selection of window for inter-pulse analysis of simple pulsed radar signal using the short time Fourier transform

Abstract: The electronic intelligence (ELINT) system is used by the military to detect, extract information and classify incoming radar signals. This work utilizes short time Fourier transform (STFT) -time frequency distribution (TFD) for inter-pulse analysis of the radar signal in order to estimate basic radar signal time parameters (pulse width and pulse repetition period). Four well-known windows functions of different and unique characteristics were used for the localization of STFT to determine their various effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This is further seen in Table 1 where the optimum SNR for the estimation of each heart rate considered is shown. The spikes in Fig.8are due to unpredictable nature of the method used when the noise is very high and mostly associated with the automatic voltage measurement algorithm using threshold just like in [25] [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further seen in Table 1 where the optimum SNR for the estimation of each heart rate considered is shown. The spikes in Fig.8are due to unpredictable nature of the method used when the noise is very high and mostly associated with the automatic voltage measurement algorithm using threshold just like in [25] [26].…”
Section: Resultsmentioning
confidence: 99%
“…In these aforementioned papers, inter-pulse analysis of radar signals are carried out to determine the time characteristics of incoming emitter signal using smoothed instantaneous energy [25] and the short time Fourier transform [26]. Unlike this work, these methods used 50 percent threshold as opposed to the 75 percent used due to the differing nature of the noise environment, signal of interest and simulation set-up.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter the effect of four various window functions of the short time Fourier transform (STFT) on the estimation of PW and PRP of a simple pulsed radar signal was investigated [12]. Results obtained showed that the lower the transition of main lobe width, the better the performance of the window function irrespective of time parameter being estimated.…”
Section: Introductionmentioning
confidence: 99%